Tinjauan Teologis dan Dampak Perceraian Menurut Matius 19:6 - Benny Andreson Situmorang; Dina Sembiring (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2022)
AbstractDivorce is a decision that is very contrary to God's will. But it is often the final decision in solving heavy and complicated problems in a marriage. This has also often been experienced by Christian families. That is why it is very important to understand the Word of God in Matthew 19:6 saying: “So then, they are no longer two but one flesh. Therefore what God has joined together, let not man separate." This is very important to discuss because of the high rate of divorce in Christian families. Where the divorce does not only affect the person concerned (husband and wife), but also involves children. Children's reactions to their parents' divorce are greatly influenced by the way parents behave before, during and after the divorce.Keywords: Review, Theological, Impact, Divorce